Effects of BaCO3 addition on the microstructure and electrical properties of La-doped barium titanate ceramics prepared by reduction-reoxidation method. Issue 1 (January 2018) - Zu, Hao; Fu, Qiuyun; Gao, Chao; Chen, Tao; Zhou, Dongxiang; Hu, Yunxiang; Zheng, Zhiping; Luo, Wei
Abstract: Effects of trace BaCO3 addition were investigated on microstructure and electrical properties of La-doped BaTiO3 ceramics prepared via reduction-reoxidation method. The addition of BaCO3 could effectively facilitate the densification and grain growth of ceramics. SEM images suggested that numerous pores presented in ceramics due to the decomposition of BaCO3 to expel generated CO2 gas. The presence of pores promoted reoxidation of the reduced ceramics. As a result, lowering room-temperature (RT) resistivity and improving PTCR jump were simultaneously achieved as suitable amount of BaCO3 was added. An optimal addition of 0.3 mol% BaCO3 led to a low RT resistivity of about 28 Ω cm and a PTCR jump up to 10 3.7 after ceramics were fired at 1100 °C in high-purity N2 and reoxidized at 800 °C in air.